Characterization of Arabidopsis thaliana R2R3 S23 MYB Transcription Factors as Novel Targets of the Ubiquitin Proteasome-Pathway and Regulators of Salt Stress and Abscisic Acid Response - Beathard, Chase; Mooney, Sutton; Al-Saharin, Raed; Goyer, Aymeric; Hellmann, Hanjo (Frontiers in Plant Science, 2021)
Rapid response to environmental changes and abiotic stress to coordinate developmental programs is critical for plants. To accomplish this, plants use the ubiquitin proteasome pathway as a flexible and efficient mechanism to control protein stability and to direct cellular reactions. Here, we show that all three members of the R2R3 S23 MYB transcription factor subfamily, MYB1, MYB25, and MYB109, are degraded by the 26S proteasome, likely facilitated by a CUL3-based E3 ligase that uses MATH-BTB/POZ proteins as substrate adaptors. A detailed description of MYB1, MYB25, and MYB109 expression shows their nuclear localization and specific tissue specific expression patterns. It further demonstrates that elevated expression of MYB25 reduces sensitivities toward abscisic acid, osmotic and salt stress in Arabidopsis, while downregulation of all S23 members results in hypersensitivities. Transcriptional profiling in root and shoot of seedlings overexpressing MYB25 shows that the transcription factor widely affects cellular stress pathways related to biotic and abiotic stress control. Overall, the work extends our knowledge on proteins targeted by CUL3-based E3 ligases that use MATH-BTB/POZ proteins as substrate adaptors and provides first information on all members of the MYB S23 subfamily.